2002
DOI: 10.1093/nar/gkf477
|View full text |Cite
|
Sign up to set email alerts
|

C.EcoO109I, a regulatory protein for production of EcoO109I restriction endonuclease, specifically binds to and bends DNA upstream of its translational start site

Abstract: The EcoO109I restriction-modification system, which recognizes 5'-(A/G)GGNCC(C/T)-3', has been cloned, and contains convergently transcribed endonuclease and methylase. The role and action mechanism of the gene product, C.EcoO109I, of a small open reading frame located upstream of ecoO109IR were investigated in vivo and in vitro. The results of deletion analysis suggested that C.EcoO109I acts as a positive regulator of ecoO109IR expression but has little effect on ecoO109IM expression. Assaying of promoter act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…The ORF therefore was designated the C.EcoT38I gene, which might produce a control protein for the EcoT38I R-M gene. Neither a conserved DNA sequence element termed a "C box," which is found immediately upstream of some C genes and is at least one target of C.PvuII binding (31), nor a C.EcoO109I-binding sequence (17) was found upstream of the C.EcoT38I gene translational start site. The GϩC contents of the R.EcoT38I, M.EcoT38I, and C.EcoT38I genes were 35, 42, and 38%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORF therefore was designated the C.EcoT38I gene, which might produce a control protein for the EcoT38I R-M gene. Neither a conserved DNA sequence element termed a "C box," which is found immediately upstream of some C genes and is at least one target of C.PvuII binding (31), nor a C.EcoO109I-binding sequence (17) was found upstream of the C.EcoT38I gene translational start site. The GϩC contents of the R.EcoT38I, M.EcoT38I, and C.EcoT38I genes were 35, 42, and 38%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA fragment was excised with ApaI and SpeI and then ligated into ApaI/SpeIdigested pMCLTerAR (17). The activity of NADPH-dependent aldehyde reductase (AR1) (EC 1.1.1.2) at 37°C was determined by measuring the rate of decrease in the absorbance at 340 nm as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…Other groups, such as that exemplified by C.Csp231I and C.EcoO109I, have very different recognition sites and their structures are currently unknown. Kita et al (2002) have previously identified the recognition sequence of C.EcoO109I as a 15 bp sequence comprising two palindromic pentanucleotides separated by a nonbinding pentanucleotide sequence, 5 0 -CTAAG(N 5 )CTTAG-3 0 , located 47 bp upstream of the C gene start codon. This conforms to the sequence motif identified for both C.Csp231I and C.EcoO109I by bioinformatic analysis (Sorokin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1. The C boxes have been shown in several cases, including PvuII (60), EcoRV (64), EcoO109I (27), and BamHI (J. Brooks, personal communication), to be bound by the cognate C protein. For PvuII, it has been shown that mutation of the C box can abolish this binding (60).…”
mentioning
confidence: 99%